2019
DOI: 10.5799/jmid.537133
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Pattern of Antibiotic Usage among Students of a Nigerian University

Abstract: Objective: Antibiotic resistance is a major public health issue globally fueled largely by its misuse. Controlling this problem would require an understanding of the levels of awareness of the population towards antibiotics. This study assessed the baseline information on the knowledge, attitude and practice towards antibiotics among university students in Ogun State Nigeria. Methodology: A cross-sectional study was conducted between January and March 2016 among a convenience sample of undergraduate students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…This improved knowledge might be important efforts to reduce misconceptions and misguided expectations contributing to inappropriate antibiotic use. This study is also in agreement with Ayepola et al [29] whose findings iterated the fact that lower level students had more knowledge on antibiotic resistance than their counterparts with higher level of education. This gives an indication that, people with high level of education are either saturated with knowledge or they do not pay much attention to educational campaigns on antibiotic resistance.…”
Section: Discussionsupporting
confidence: 93%
“…This improved knowledge might be important efforts to reduce misconceptions and misguided expectations contributing to inappropriate antibiotic use. This study is also in agreement with Ayepola et al [29] whose findings iterated the fact that lower level students had more knowledge on antibiotic resistance than their counterparts with higher level of education. This gives an indication that, people with high level of education are either saturated with knowledge or they do not pay much attention to educational campaigns on antibiotic resistance.…”
Section: Discussionsupporting
confidence: 93%
“…22 As it is a condition for which a bacterium loses its response towards an antimicrobial, 86.6% agreed that antibiotic misuse leads to resistance and 67.7% agreed on taking a full course of antibiotic treatment irrespective of symptomatic improvement to prevent the development of antimicrobial resistance. This is comparable with the study findings from Nigeria (63.3%), Pakistan (62.5%), and India (54.5%).- 21,23,24 However, it is low compared to the study done in Italy where more than 90% of respondents were agreed that misuse leads to resistance (98%), a full course of treatment is mandatory despite symptoms improving (94.8%), and who knew that antibiotic resistance can occur when the bacteria lose sensitivity to the agent (93.9%). The discrepancies could have resulted from the fact that in developed nations, students can get access to health information even before formal academic education from different sources, which is less likely in developing countries like Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…Focusing on the experiences of students with antibiotics use showed that about 40% of participants had antibiotics without a prescription. This attitude has also been reported in study in Jordan and Nigeria whereas 51.0% and 98.5% of the participants used antibiotics without a prescription, respectively [17,19]. Comparable numbers have also been reported in several studies in Europe among general populations where rates ranged from 10 -45% in Britain and Greece, respectively [20].…”
Section: Discussionsupporting
confidence: 73%
“…Compared to study conducted in Jordan, the respondents reported using antibiotics for treatment of common cold (61.0%) and cough with fever (59.8%) [9]. A similar study was conducted in Nigeria showed that about 35.0% of Nigerian students use antibiotics to treat cold [17]. Results from study in Benghazi University (east part of Libya) included 180 medical students showed about 45.0% of them used antibiotics for treatment of flu or runny nose illnesses [15].…”
Section: Discussionmentioning
confidence: 98%